KEEFEKTIFAN PELATIHAN KEBERMAKNAAN HIDUP TERHADAP PENURUNAN TINGKAT DEPRESI PADA LANSIA DI PANTI WREDHA DHARMA BAKTI SURAKARTA - Edwin Trisnapati, I Kadek; Yuliadi, Istar; Priyatama, Aditya Nanda (Jurnal Ilmiah Psikologi Candrajiwa, 2012)
ABSTRACT THE EFFECTIVENESS OF THE MEANING OF LIFE TRAINING TO DECREASE THE LEVEL OF  DEPRESSION  OF THE  ELDERLY PEOPLE  IN DHARMA BAKTI SURAKARTA NURSING HOME I Kadek Edwin Trisnapati Universitas Sebelas Maret Surakarta   Most problem that held to the elderly people was depression. The highest incident of depression happened to the erlderly people living in nursing home. Depression can be defined as a period of human feeling function distortion that was sad and depressed accompanied with various symptoms. A skill that will be expected able to decrease the level of depression of the elderly people by inventing the meaning of life. The meaning of life can be defined as something that was considered as an important and a valuable thing, and gave a special value for someone. This research purposed to know about the effectiveness of the meaning of life training in decreasing the level of depression of the elderly people in Dharma Bakti Surakarta Nursing Home. The meaning of life training can be defined as short term education process using systematic and organized procedure to help someone to achieve and to fill the purpose of life, so that someone will be able to decrease the level of depression into the more qualified and happier life. The subjects in this research consist of 10 elderly people. The design of this research was experimental design called pretest-posttest control group design with each groups that was the experimental group and  the control group consist of 5 people. The experimental group was given the meaning of life training three times meeting by using methods such as presentation and discussion, case study, role play, simulation and game, and exercise. The data collection methods was done by using the book of training and Geriatric Depression Scale (GDS). The data was analyzed by using nonparametric statistic technique such as 2 sample Independent Kolmogorov-Smirnov test and Wilcoxon test with computerized help SPSS version 16.0 for MS Windows program. Based on the result of 2 Independent Sample Kolmogorov-Smirnov test earned z-value 1,581 and probability (p) 0,013 (p<0,05). In addition, the result of Wilcoxon test earned z-value -2,060 and probability (p) 0,039 (p<0,05). The result showed that the meaning of life training is effective to decrease the  level of depression of the  elderly people in Dharma Bakti Surakarta Nursing Home. Keywords: the meaning of life training, the level of depression of elderly people in  Dharma Bakti Surakarta Nursing Home